European experience of land resource potential development in the conditions of globalization - Chumachenko А.; Kryvoviaz, Y.; Zhuk, O. (Land Management, Cadastre and Land Monitoring, 2021)
The article analyzes the use of land resources of countries in the context of globalization. Investment-attractive regions have been identified, the socio-economic and political conditions of which contribute to the seizure of land by foreign investors. Sources of food security of countries with developed economies are substantiated. Peculiarities of formation of land and resource space of European neo-colonial countries are determined. One of the most important historical events in the political and socio-economic dimensions of the world was colonialism, associated with the development of capitalism. In the book, Eric Wolfe, "Europe and People Without History", describes in detail the global expansion of the borders of European states in order to control both human and natural resources, as well as to expand global development and promote Christianity. European colonialism became an early form of globalization that shaped most of the world’s current political borders. In this way, technologies, food and ideas based on the colonial countries - Britain, Spain, France, Portugal and the Netherlands, etc. were transported. The main goal is to use the limited resources of the colony country and make a profit. This approach is called neocolonialism (corporate colonialism), just as classical European colonialism aims at the comprehensive exploitation of natural resources, labor, and markets for superprofits. Key words: territory, land use, land acquisition, food security, agricultural land, land.